Characterization of mouse embryonic fibroblasts derived from Rassf6 knockout mice shows the implication of Rassf6 in the regulation of NF‐κB signaling. (1st November 2021) - Morishita, Mayu; Arimoto‐Matsuzaki, Kyoko; Kitamura, Masami; Niimura, Kyohei; Iwasa, Hiroaki; Maruyama, Junichi; Hiraoka, Yuichi; Yamamoto, Kohei; Kitagawa, Masanobu; Miyamura, Norio; Nishina, Hiroshi; Hata, Yutaka
Abstract: RASSF6 is a member of the tumor suppressor Ras association domain family (RASSF) proteins. We have reported using human cancer cell lines that RASSF6 induces apoptosis and cell cycle arrest via p53 and plays tumor suppressive roles. In this study, we generated Rassf6 knockout mice by CRISPR/Cas technology. Contrary to our expectation, Rassf6 knockout mice were apparently healthy. However, Rassf6 ‐null mouse embryonic fibroblasts (MEF) were resistant against ultraviolet (UV)‐induced apoptosis/cell cycle arrest and senescence. UV‐induced p53‐target gene expression was compromised, and DNA repair was delayed in Rassf6 ‐null MEF. More importantly, KRAS active mutant promoted the colony formation of Rassf6 ‐null MEF but not the wild‐type MEF. RNA sequencing analysis showed that NF‐κB signaling was enhanced in Rassf6 ‐null MEF. Consistently, 7, 12‐dimethylbenz(a)anthracene (DMBA) induced skin inflammation in Rassf6 knockout mice more remarkably than in the wild‐type mice. Hence, Rassf6 deficiency not only compromises p53 function but also enhances NF‐κB signaling to lead to oncogenesis. Abstract : We analyzed mouse embryonic fibroblasts derived from Rassf6 knockout mice and found that p53 signaling is compromised, whereas NF‐κB signaling is enhanced.